Identificação de antígenos salivares imunogênicos de triatomíneos e avaliação de sua eficiência como marcadores de contato para Rhodnius prolixus (Stal, 1859) (Hemiptera: Reduviidae): o papel da apirase salivar - Luciana Ramos Dias (2012)
Triatomines bugs are important haematophagous insects and vectors of Trypanosoma cruzi, the etiologic agent of Chagas disease in America. Identification of triatomine infestations and control are the main procedures recommended by the Chagas disease Control Program (PCChD). The current methodology used for entomological inquiries is considered expensive and demands well trained workers. Thus, it is important to develop alternative tools to investigate triatomine infestations. Due to the direct contact between the saliva and the host immune system, the monitoring of the level of antibodies anti-saliva in persons from endemic areas would be a good alternative for entomological inquiries. Therefore, the present work aimed at the identification of immunogenic salivary antigens to evaluate their use as contact markers for triatomines. For such, we exposed groups of mice to low and high infestations of different triatomine species. After that, the most immunogenic antigens in mices sera were identified by immunoenzimatic assays (ELISA) and Western Blot. The most immunogenic antigens were purified and evaluated for cross reaction among the species of triatomines by using ELISA. The results showed that the mice exposed to low and high infestations by R. prolixus and Triatoma infestans developed an anti-saliva specie-specific response. Responses to low and high infestations were not different in the serum of mice exposed to R. prolixus saliva. The western blot results showed that a protein with 48.4 kDa and another with 18.2 kDa were the most immunogenic molecules in R. prolixus saliva. The 48.5 kDa protein was purified and identified as a salivary apyrase. ELISA showed that the apyrase from R. prolixus can be recognized by antibodies produced in mice exposed to R. prolixus infestations, but it cannot be recognized by serum of mice exposed to T. infestans or Triatoma brasiliensis infestations. By searching the NCBI databases, we identified two types of apyrase expressed in R. prolixus salivary glands: one intracellular and another secreted (probably the antigen with 48.5 KDa founded in the Western blot). Our results indicate the salivary apyrase from R. prolixus as a promising contact marker for the triatomine infestations. Nevertheless, other experiments must be carried out to encounter other salivary antigens adequate to avoid cross reactions with salivary proteins from triatomine and other arthropods.